Boosting highly transparent and conducting indium zinc oxide thin films through solution combustion synthesis: influence of rapid thermal annealing. (7th September 2018) - Ullah, Sana; Branquinho, Rita; Santa, Ana; De Matteis, Fabio; Martins, Rodrigo; Davoli, Ivan; Gonçalves, Gonçalo; Fortunato, Elvira
Abstract: IZO thin films with In:Zn ratio of 7:3 and 3:7 were prepared by solution combustion synthesis of metal oxide nitrates and influence of post-deposition rapid thermal annealing (RTA) was studied. Individual 0.5 M indium and zinc oxide precursor solutions were mixed in 7:3 and 3:7 compositions. XRD analysis showed IZO 7:3 composition has only cubic bixbyite In2 O3 structure while IZO 3:7 composition showed both hexagonal wurtzite ZnO and cubic bixbyite In2 O3 phases. SEM and AFM analysis showed low roughness for IZO 7:3, rms < 2 nm whereas for IZO 3:7 composition surface roughness was >22 nm due to phase segregation. UV/ViS/NIR analysis showed transparency range desirable of transparent conductors for both compositions. Post-deposition RTA treatment resulted in high conductivity single phase IZO 7:3 films. Segregation of phases enhanced carrier scattering resulting in decreased mobility for IZO 3:7 films. Best performing IZO films demonstrated low resistivity 7.66 × 10 −3 Ohm cm and high carrier concentration 5.09 × 10 19 /cm 3 after 10 min RTA at 600 °C. These results demonstrate combustion synthesis and RTA are successful for development of films with enhanced conductivity and transparency through low cost vacuum-free synthesis reducing indium content for applications in photovoltaic devices, flat panel displays and transparent electronics.